2019
DOI: 10.12968/ijpn.2019.25.7.316
|View full text |Cite
|
Sign up to set email alerts
|

Sleep assessment and interventions for patients living with cancer from the patients' and nurses' perspective

Abstract: Background: Difficulty sleeping is a common symptom for patients living with cancer that significantly affects their lives. However, although sleep disorders are common, it is an overlooked problem in cancer care. Purpose: This study assessed the prevalence of sleep disturbances among patients living with cancer, and assessed the adequacy of sleep assessment and intervention for patients from both nurses' and patients' perspectives. Method: Descriptive, cross-sectional and correlational design was used in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Of the reviewed studies, 9 were quantitative studies (De Almeida Tavares et al, 2015; Eliassen & Hopstock, 2011; Erwin et al, 2019; Gellerstedt et al, 2019a; Hofhuis et al, 2012; Hofhuis et al, 2018; Khater et al, 2019; Radtke et al, 2014; Vincensi, 2016) and 6 were qualitative studies (Gellerstedt et al, 2015; Honkavuo, 2018; Hopper et al, 2015; McIntosh & MacMillan, 2009a; Salzmann‐Erikson et al, 2016; Ye et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the reviewed studies, 9 were quantitative studies (De Almeida Tavares et al, 2015; Eliassen & Hopstock, 2011; Erwin et al, 2019; Gellerstedt et al, 2019a; Hofhuis et al, 2012; Hofhuis et al, 2018; Khater et al, 2019; Radtke et al, 2014; Vincensi, 2016) and 6 were qualitative studies (Gellerstedt et al, 2015; Honkavuo, 2018; Hopper et al, 2015; McIntosh & MacMillan, 2009a; Salzmann‐Erikson et al, 2016; Ye et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This study used a valid and reliable tool, the Geriatric Nursing Knowledge/Attitudes (GNKA) subscale of the Geriatric Institutional Assessment Profile (GIAP), to measure nurses' knowledge and attitudes related to preventing pressure ulcer, using restraint, incontinence care and managing sleep disturbance. Most studies pilot‐tested used instruments to determine validity (Eliassen & Hopstock, 2011; Gellerstedt et al, 2019a; Hofhuis et al, 2012; Hofhuis et al, 2018; Khater et al, 2019;Radtke et al, 2014; Vincensi, 2016). One study described missing data and provided an appropriate rationale (Eliassen & Hopstock, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is of utmost importance that oncology nurses have knowledge of sleep assessment to provide good symptom control. However, a study on sleep assessment in patients living with cancer, discovered that few nurses assessed sleep patterns, undertook further assessment and investigations for patient’s sleep problems, or reassessed the patients sleep patterns in case the patient complained of non-efficacy of the interventions [ 84 ].…”
Section: Implications For Clinical Practice and Future Researchmentioning
confidence: 99%
“…Several reasons might explain the lack of sleep assessment among health care providers. Sleep disturbances might be considered a low-priority problem compared to the cancer itself, or because of a lack of sleep assessment protocols or guidelines [ 84 , 85 ]. Interestingly, a literature review on nurses’ perceptions of sleep in the intensive care unit revealed that intensive care unit nurses lack a complete understanding of the importance of sleep [ 86 ].…”
Section: Implications For Clinical Practice and Future Researchmentioning
confidence: 99%